Cardiovascular Outcomes Associated With Hypoplastic Left Heart Syndrome Versus Other Types of Single Right Ventricle: A Multicenter Study - Nabil Dib; Nancy Poirier; Michelle Samuel; Sewanou Hermann Honfo; Ali Zaidi; Alexander R. Opotowsky; François‐Pierre Mongeon; Blandine Mondésert; Joseph Kay; Reda Ibrahim; Robert M. Hamilton; Anne Fournier; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The univentricular heart with a predominant right ventricle morphology (uRV) has been associated with a higher rate of adverse cardiovascular events. It remains to be determined whether the specific type of uRV influences outcomes. Methods and Results A North American multicenter retrospective cohort study was conducted by the Alliance for Adult Research in Congenital Cardiology on individuals with a uRV and total cavopulmonary connection Fontan. The incidence of a composite outcome consisting of all‐cause mortality, cardiac transplantation, atrial arrhythmias, or thromboembolic events was compared among patients with Fontan palliation who had hypoplastic left heart syndrome (HLHS) versus other forms of uRV (non‐HLHS). All components of the composite outcome were classified by a blinded adjudicating committee. Competing risks were taken into account in time‐to‐event analyses. A total of 171 patients with uRV of whom 76 (44.4%) had HLHS were followed for 10.2±5.7 years. The composite outcome occurred in 7.1 versus 2.1 cases per 100 person‐years in patients with HLHS versus non‐HLHS (P<0.0001). In multivariable analyses, HLHS was associated with a significantly higher risk of the composite outcome (hazard ratio [HR], 6.13 [95% CI, 2.92–12.69], P<0.001). Moreover, HLHS was associated with significantly higher rates of all components of the primary outcome. Conclusions Among patients with a uRV and Fontan palliation, HLHS is associated with a significantly higher rate of adverse cardiovascular events.